Identifying Preventive Maintenance Guidelines for Rice Combine Harvester with Application of Failure Mode and Effect Analysis Technique - Kanchana, Rapee; Triwanapong, Surat; Kimapong, Kittipong (Frontiers in Engineering Innovation Research, 2020)
This research aims to study the risk factors of the rice combine harvester by using failure mode and effect analysis (FMEA) technique. The research methodology began with classifying failure modes and causes during harvesting rice. After that, each type of failure mode was evaluated and calculated a risk priority number (RPN), then, RPN is sorted in descending order. Machine parts belonging to a high risk group were investigated a root cause of failure occurrence and then determined preventive maintenance guidelines. From data analysis, it illustrated that there were five types of risk classified as a high risk group; F21 wear of chain surface, F19 wear of rubber O-ring, F14 wear of ball roller surface, F10 sprocket gear broken and F12 lead wheel broken. This high risk group implied that if some failures occur, the combine harvester can be stopped which caused harvesting operation interruption. As a result, a development of preventive maintenance guidelines was needed. This research provides the self-preventive maintenance guidelines for farmer who used the rice combine harvester which the results of self-preventive maintenance help extending the useful life of each parts and enhancing work efficiency of the rice combine harvester.